Perjanjian Sewa Menyewa Tanah Hak Milik Tanpa Batas Waktu Antara WNI dengan WNA menurut Hukum Positif Indonesia - Reffa Rafelya; Lina Jamilah (Bandung Conference Series: Law Studies, 2022)
Abstract. An agreement is an act in which one or more persons bind themselves to one or more persons. The conditions for the validity of the agreement according to Article 1320 of the Civil Code "there is an agreement between those who bind themselves, the ability to make an engagement, the object of the agreement, and a lawful cause". In practice, there is a land lease agreement that lasts for life, namely in the land lease agreement dated January 5, 2005 where Mrs.Ida Ayu Eka, an Indonesian citizen as the owner of the lease, and Mr.Renehan Michael John, a foreign citizen as the tenant. So this study aims to find out and understand how the Land Lease Agreement with Unlimited Time Between Indonesian Citizens and Foreign Citizens According to Positive Law in Indonesia and to know and understand the legal consequences of Land Lease Agreements without a Time Limit between Indonesian Citizens and Foreign Citizens according to Positive Law in Indonesia. The research method used is a normative juridical approach with analytical descriptive specifications with qualitative analysis methods. The legal consequences of this agreement are invalid because they don’t meet the legal requirements of the agreement because they have violated the objective requirements of Article 1320 of the Civil Code. If the conditions regarding a certain matter and a lawful cause (objective conditions) are not fulfilled, then an agreement is null and void, meaning that from the start it is considered that there is no agreement or is null and void. Abstrak. Perjanjian adalah suatu perbuatan dimana satu orang atau lebih mengikatkan dirinya terhadap satu orang atau lebih. Syarat sahnya perjanjian sesuai Pasal 1320 KUHPerdata “adanya kesepakatan mereka yang mengikatkan dirinya, kecakapan untuk membuat suatu perikatan, adanya objek perjanjian, dan suatu sebab yang halal”. Pada perakteknya terdapat perjanjian sewa menyewa tanah hak milik yang dilangsungkan seumur hidup, yaitu pada perjanjian sewa menyewa tanah tertanggal 5 Januari 2005 dimana Nyonya Ida Ayu Eka, Warga Negara Indonesia selaku pemilik sewa dan Tuan Renehan Michael John, Warga Negara Asing selaku penyewa. Maka penelitian ini bertujuan untuk mengetahui dan memahami Bagaimana Perjanjian Sewa Menyewa Tanah Hak Milik Tanpa Batas Waktu Antara WNI Dengan WNA Menurut Hukum Positif di Indonesia dan Untuk mengetahui dan memahami Akibat Hukum Perjanjian Sewa Menyewa Tanah Tanpa Batas Waktu Antara WNI Dan WNA menurut Hukum Positif di Indonesia. Metode penelitian yang digunakan adalah metode pendekatan yuridis normatif dengan spesifikasi deskriptif analitis dengan metode analisa secara kualitatif. Akibat Hukum dari perjanjian ini tidak valid karena tidak memenuhi syarat sahnya perjanjian karena telah melanggar syarat obyektif Pasal 1320 KUHPerdata. Jika syarat mengenai suatu hal tertentu dan suatu sebab yang halal (syarat obyektif) tidak dipenuhi, maka suatu perjanjian batal demi hukum maksudnya sejak awal dianggap tidak ada perjanjian atau batal demi hukum.